Safety and tolerability of 6-month supplementation with a vitamin D, calcium and leucine-enriched whey protein medical nutrition drink in sarcopenic older adults - Bauer, Jürgen M.; Mikušová, Lucia; Verlaan, Sjors; Bautmans, Ivan; Brandt, Kirsten; Donini, Lorenzo M.; Maggio, Marcello; Mets, Tony; Wijers, Sander L. J.; Garthoff, Jossie A.; Luiking, Yvette; Sieber, Cornel; et al. (Aging clinical and experimental research, 2020)
Safety and tolerability of prolonged supplementation with a vitamin D, calcium and leucine-enriched whey protein medical nutrition drink (WP-MND) was evaluated in sarcopenic older adults.